Some Commutative Neutrix Convolutions Involving the Fresnel Integrals - Fisher, Brian; Nonlaopon, Kamsing; Sritanratana, Gumpon (Sarajevo Journal of Mathematics, 2024)
The Fresnel cosine integral C(x), the Fresnel sine integral S(x) and the associated functions C_+(x), C_-(x), S_+(x) and S_-(x) are defined as locally summable functions on the real line. Some convolutions and commutative neutrix convolutions of the Fresnel sine integral and its associated functions with x^r are evaluated. 1991 Mathematics Subject Classification. 33B10, 46F10